Засоби інфографіки, які доречні для друкованих видань - Середа, Г. В. (ХНУРЕ, 2024)
The article discusses the means of infographics, which are appropriate for printed publications. It is described which decorative elements can be used, how to adjust them to the content of the displayed information. And also how to make them so that they will be easy to print. Top design rules for creating infographics for good print in books.
Keywords: засоби інфографіки; друковане видання